Kinetics studies on the Micellar Catalyzed Reaction of Phenacyl Bromide with Phenol-Triethylamine in Aqueous-Organic Mixed Solvents - Nallu, M.; Thangadurai, S. (Asian Journal of Chemistry, 2010)
Kinetics of the reaction between phenacyl bromide and phenol-triethylamine in the presence of sodium lauryl sulphate (NaLS) as surfactant in aqueous-organic mixed solvents at 30°C have been studied conductometrically using Guggenheim's method under pseudo-first-order conditions. Etherification takes place in the presence of micelles, whereas quaternization in its absence. It is supported by product analysis.